La transformation des grains - Cruz , Jean-François (éditions Quae, 2020)
This book covers several aspects of grain processing and complements the book on grain preservation in the same collection. It presents different processing methods, targeting mainly small and medium-sized enterprises as the main players in food processing systems in the South countries.